Structural theory - Sutherland, Hale.; Bowman, Harry Lake. (New York : John Wiley and Sons, 1949)
Structural Theory by Sutherland and Hale is a comprehensive book that delves into the fundamental principles of structural analysis and design. The book covers a wide range of topics, from the basic concepts of structural mechanics to the advanced techniques used in the design of complex structures.The book begins with an introduction to the principles of statics and mechanics of materials, which are essential for understanding the behavior of structures under different loads. It then moves on to the analysis of statically determinate and indeterminate structures, including beams, frames, and trusses.The authors also cover the design of structural members, such as columns, beams, and connections, using the latest design codes and standards. The book includes examples and problems that help readers apply the concepts they have learned to real-world situations.In addition, Structural Theory covers advanced topics such as the analysis of dynamic loads, the design of earthquake-resistant structures, and the use of computer-aided design tools in structural engineering.Overall, Structural Theory is an essential resource for students, practicing engineers, and researchers who want to deepen their understanding of structural analysis and design. It provides a comprehensive and practical approach to the subject, making it an invaluable reference for anyone working in the field of structural engineering. This scarce antiquarian book is a facsimile reprint of the old original and may contain some imperfections such as library marks and notations. Because we believe this work is culturally important, we have made it available as part of our commitment for protecting, preserving, and promoting the world's literature in affordable, high quality, modern editions, that are true to their original work.
Includes index.
Keywords: Strength of Materials; Structural Analysis; Load Distribution; Stresses and Strains; Beams and Columns; Structural Stability